A Translation Analysis On Noun Phrase In Endless Night Into Malam Tanpa Akhir - Rohmawati, Novita; , Dr. Dwi Haryanti, M. Hum; , Drs. Djoko Srijono, M. Hum (2015)
The research studies about the translation analysis of noun phrase in Endless Night into Malam Tanpa Akhir. The aims of this research is to classify the noun phrase translation variations found in Endless Night and to describe the readability of noun phrase translation variations found in Endless Night. The method of collecting data is documentation and interviewing. The result of the research shows that there are 35 translation variations of noun phrases in Endless Night novel and its translation. That translation variations come from 7 types of noun phrases. From 502 data of noun phrases, there are 243 or 48% data of NP1 variation that is translated into noun, verb, adjective, adverb, NPa, NPb and deletion of NP1; there are 21 or 4.2% data of NP2 variation that is translated into NPa, NPb, NPc, NPg, verb, and noun; there are 167 or 35.2% data of NP3 variation that is translated into noun, adjective, verb, NPa, NP, NPc, NPg, and deletion of NP3; there is only one or 0.2% data of NP4 that is translated into NPa; there are 44 or 9.6% data of NP5 variation that is translated into NPa, NPb, NPg, noun, adjective, and deletion of NP5; there are of 25 or 4.6% data of NP7 that is translated into NPa, NPb, NPc, NPd, NPg, and adjective; there is only one or 0.2% data of NP8 in Endless Night novel that is translated into adverb. In readability of the translation, there are 3 grades to assess the translation. The first grade is 2.75 - 3. In this first grade, there is 279 or 56.2% data of noun phrases translation that have high readability level. The second grade is 2 - 2.74. In this grade, the writer finds 223 or 43.8% data of noun phrases translation from three respondents. So, it is categorized as noun phrase that has medium readability level. The last grade is 1 - 1.99. Data of noun phrases translation are not found in the last grade..